A Systematic Review of Mobile Banking, Fintech Innovations, and Regulatory Gaps to Achieve Financial Inclusion in the Philippines - Velez, Giovanni (Journal of Interdisciplinary Perspectives, 2025)
Digital financial inclusion has become vital in bridging economic disparities, particularly in the Philippines, where 68% of adults remained unbanked as of 2021. This systematic review, adhering to PRISMA guidelines, synthesizes 26 studies (2014–2024) to evaluate how mobile banking, fintech innovations, and regulatory frameworks contribute to financial inclusion in marginalized communities. Findings reveal that platforms like GCash have considerably enhanced access to financial services, reducing cash dependency by 41% in urban and 29% in rural areas. However, structural inequities persist, including the digital divide in regions like Visayas and Mindanao, low financial literacy (only 34% of low-income users understand digital security), and gender gaps (women-owned MSMEs represent 22% of fintech borrowers despite comprising 39% of entrepreneurs). Regulatory frameworks like the National Retail Payment System improved transaction volumes but struggled with fragmentation and rural implementation. The COVID-19 pandemic accelerated digitization yet exacerbated exclusion for low-literacy populations. The study emphasizes the need for multidimensional strategies: infrastructure investments in rural connectivity, gender-responsive fintech designs, regulatory harmonization, and community-driven literacy programs. Future research must address longitudinal impacts, intersectional barriers, and policy effectiveness to achieve equitable financial inclusion in the Philippines.